Phylogeny of the Ficus sarmentosa complex (Moraceae) uncovered an omitted species and the rank elevation of F. pubigera var. maliformis - Zhang, Zhen; Chen, Yi-Jia; Mei, Li; Zou, Lu; Zhang, Mei-Jiao; Li, Hong-Qing; Zhang, De-Shun (Phytotaxa, 2023)
The common breakdown of one-to-one obligate mutualism renders that the hybridization and introgression are relatively universal in the evolutionary history of Ficus, which makes Ficus a difficult taxon taxonomically. The Ficus sarmentosa complex includes 10 species and 10 varieties, and multiple taxonomical issues exist so far due to overlapping and plastic morphological traits together with frequent gene flow. To explore the evolutionary history and taxonomy of the F. sarmentosa complex, three nuclear loci and comprehensive sampling were implemented. The phylogenetic result supported the species statuses of F. pumila, F. howii, F. dinganensis, F. pubigera, and F. anserina. Whereas, the phylogenetic relationships between the varieties and three allies of F. sarmentosa still remain unclear based on the current data. Besides, F. pubigera var. maliformis was elevated as the species ranks and then was named F. yunnanensis. At last, an omitted species was uncovered in the complex and then described with named F. muricata.